Influence of Substrate to Biomass Ratio (F /M) and pH On Microbial Stability of Activated Sludge - Mohd Said, Muhammad Afif (Universiti Teknologi Petronas, 2012)
Activated sludge contains biological floes composed of bacteria that degrade the organic matter in the waste water for its growth. The microbial stability of the activated sludge represented by the characteristics of the floes. Project is focused on activated sludge used by most operating wastewater treatment plant owned by PETRONAS. Bacteria chosen will be BIOCHEM (BCI-103) brand. The bacteria are taken from a gas processing plant located in Kerteh, Terengganu. The main objective of this project to study on the influence of two major parameters in wastewater, which are the substrate to biomass ratio or also known as food to microorganism (FIM) and pH, to the characteristics of the bacteria floes. Optimum value of F/M and pH obtained from this project will be recommended to further enhance the wastewater process control at the processing plant. Besides that, the characteristics of floes that obtained at different F 1M and pH can be served as informative data to further enhance the understanding of the bacteria used. Nowadays, with the increasing industrial activity, usage of hazardous chemicals escalates thus endangering the environment. News raised on the environment pollution especially the water pollution effecting the seas and rivers. One of the main causes of this pollution is the ineffective operation of wastewater treatment plant. Many microbially-related activated sludge solids separation problems occurred such as dispersed growth, filamentous bulking and foam formation. Existing design parameter such as sludge age, Chemical Oxygen Demand (COD), and Sludge Volume Index (SVI) can't predict the stability of the bacteria floes. These design parameters are more oriented to the final goal of releasing effluent below the standard limit set by the government. Thus, the project will focus on the study of F/M and pH as design parameters and their influence to the bacteria floes.